The Effectiveness of the Teams Games Tournament Model Using Blooket Games Media on Fourth-Grade Science Learning Outcomes - Dani, Novelita Ayu Rahma; Nafiah, Nafiah; Wahyudi, Agus; Rahayu, Dewi Widiana (FKIP - Universitas Riau, 2026)
This study examines the effectiveness of the Teams Games Tournament (TGT) cooperative learning model supported by Blooket media on student learning outcomes in Grade IV Science and Social Studies (IPAS) at SD Iskandar Said, Surabaya. The study was conducted in response to low student learning outcomes associated with the use of conventional instructional methods and limited utilization of interactive learning media. A quantitative approach was employed using a one-group pretest–posttest pre-experimental design. The research sample consisted of 25 students from Class IVA. Data were collected through learning outcome tests (pretest and posttest), observation sheets of learning implementation, and student response questionnaires. The results indicated that the mean pretest score of 48.80 increased to 85.60 in the posttest. The N-Gain value of 0.73 was categorized as high, indicating a substantial improvement in learning outcomes. Observation results showed a score of 62, categorized as good, reflecting consistent implementation of the learning model. Student response questionnaire results indicated a positive level of engagement, with a percentage of 95%. These findings suggest that the application of the TGT learning model supported by Blooket media contributes to improved learning outcomes and encourages active student participation in the learning process.